Maximizing the Standing Skyline Log Load Using a Variable Length Tagline - John Sessions (Forests, 2021)
The standing skyline continues to be a common cable logging configuration. In payload analysis it is usually assumed that the tagline (line connecting the logs to the carriage) length is held constant while yarding a turn up the skyline corridor. We show this assumption severely limits the skyline load-carrying capacity for skylines operating with partial suspension. We suggest that smart carriage technology could markedly increase the log load capacity through the use of a variable length tagline, and thus logging productivity. A methodology for estimating the log load capacity for a standing skyline with variable tagline length is presented. We illustrate that increases of 30–40 percent in log load are possible with a variable length tagline.